Value assessment of oncology drugs using a weighted criterion‐based approach. Issue 7 (20th December 2019) - Ezeife, Doreen A.; Dionne, Francois; Fares, Aline Fusco; Cusano, Ellen Laura Rose; Fazelzad, Rouhi; Ng, Wenzie; Husereau, Don; Ali, Farzad; Sit, Christina; Stein, Barry; Law, Jennifer H.; Le, Lisa; et al.
Abstract : Background: Globally, the rising cost of anticancer therapy has motivated efforts to quantify the overall value of new cancer treatments. Multicriteria decision analysis offers a novel approach to incorporate multiple criteria and perspectives into value assessment. Methods: The authors recruited a diverse, multistakeholder group who identified and weighted key criteria to establish the drug assessment framework (DAF). Construct validity assessed the degree to which DAF scores were associated with past pan‐Canadian Oncology Drug Review (pCODR) funding recommendations and European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO‐MCBS; version 1.1) scores. Results: The final DAF included 10 criteria: overall survival, progression‐free survival, response rate, quality of life, toxicity, unmet need, equity, feasibility, disease severity, and caregiver well‐being. The first 5 clinical benefit criteria represent approximately 64% of the total weight. DAF scores ranged from 0 to 300, reflecting both the expected impact of the drug and the quality of supporting evidence. When the DAF was applied to the last 60 drugs (with reviewers blinded) reviewed by pCODR (2015‐2018), those drugs with positive pCODR funding recommendations were found to have higher DAF scores compared with drugs not recommended (103 vs 63; Student t test P  = .0007). DAF clinical benefit criteria mildly correlated with ESMO‐MCBS scores (correlation coefficient, 0.33; 95% CI, 0.009‐0.59). Sensitivity analyses that varied the criteria scores did not change the results. Conclusions: Using a structured and explicit approach, a criterion‐based valuation framework was designed to provide a transparent and consistent method with which to value and prioritize cancer drugs to facilitate the delivery of affordable cancer care. Abstract : In the current study, the authors have designed a criterion‐based valuation framework using multiple perspectives, and the robustness of the tool is demonstrated when compared with past submissions. This derived score represents the overall impact of a new cancer treatment, and the quality of evidence used to generate the score.